Public participation and democratic legitimacy of rulemaking: A comparative analysis - Iztok Rakar (DANUBE: Law, Economics and Social Issues Review, 2017)
In recent years, public participation has been a frequent object of research, especially in relation to rulemaking procedures. The aim of the paper is to verify a common thesis, that public participation is a means for enhancing democratic legitimacy in rulemaking. In order to do so, the author defines legitimacy and legitimation, presents models of the democratic legitimacy of the executive and compares monistic and pluralistic understanding of democracy. The author then analyzes standpoints of American, English and German legal theory and case law and proposes a possible solution to the main research question.
Keywords: 330; Rulemaking; Public Participation; Legitimacy; Democracy